COMPARISON OF PHYSIOLOGICAL RESPONSES BETWEEN INTERVAL METHOD, 8V8 AND 4V4 GAMES AND TECHNICAL-TACTICAL EXERCISE IN SOCCER TRAINING - Ioannis ISPIRLIDIS; Vasilios GEORGOULIS; Dumitru Rareş CIOCOI-POP; Konstantinos FAMISSIS; Georgios DIMITROPOULOS; Paschalis KIRIALANIS; Aikaterini PAPADIMITRIOU (Cluj University Press, 2019)
Purpose: Football is a sport that requires strong player demands. During the workout of improving the endurance are used exercises with or without the ball as well as racing games. In the present study we analyzed the burden of 4 different types of exercise(intermittent without the ball, 8v8 game, 4v4 game, and technical exercises) to determine which kind is best suited for improving the specific endurance. Material: The sample was 5 professional players (mean ± SD) of age (26± 2.9 years), height (1.79 ± 0,03m) and body weight (75± 3 kg). Prior to the experiment, a Test to determine the anaerobic threshold was performed. Measurements of lactic acid were made by using the Dr Lange photometer, while heart rate measurements by using POLARFT60 portable heart ratemeters. Results: The assumption of normal distribution was verified using the Kolmogorov-Smirnov test and it was found that in all variables the data follows the normal distribution. For the statistical treatment of the data a Analysis of Variance for repeated measure was used and for the detection of statistically significant differences between the measurement conditions was used the LSD multiple comparison test. The level of significance was defined as p<0.05. The analysis of the results showed that there is a statistically significant difference between the different types of exercise: a) the concentration of lactic acid (F3,12) = 11,053, p<0,05), b) in the min of heart rate >4mmol lactic acid (F(3,12)= 21,331 p<0,05). c) in the min of the heart rate at 3-4 mmol lactic acid (F(3,12)= 3,584, p<0,05) d) in the min of heart rate at 2-3mmol lactic acid (f(3,12= 4,310,p <0,05) and e) averages of the heart rate relative to ANK (F (3,12)= 25,404, p<0,05). Conclusion: It seems that the 4 different types of exercise cause different metabolic processes of lactic acid production as well as different heart rate responses. The intermittent and 4v4 game schedule is better suited to improving the endurance the 8v8 game is suitable for improving aerobic endurance, while technical-tactical exercises do not produce sufficient stimuli to improve endurance but involve speed stimuli.